Enhancing Students' Chemical Literacy with Environmental Problem-Based Learning Models through Lesson Study Practices - Trisnawati, Ade; Permatasari, Adina Amelia (Universitas Pendidikan Mandalika, 2025)
The purpose of this study was to determine the increase in students’ chemical literacy skills after being taught an environmental problem-based learning model through lesson study practices using quantitative descriptive analysis methods. This research flow uses the Lesson Study cycle stages consisting of Plan, Do, See, and Redesign. The subjects of this study were 17 first semester students of the Chemical Engineering and Physics Education Study Program at PGRI Madiun University who took basic chemistry courses. The data collected in this study were in the form of observation data and tests that measured students’ chemical literacy skills. The results showed that students’ chemical literacy skills were at a moderate level. In the Knowledge of Science and Chemical Content and Chemistry in Context aspects, the number of students who understood the concept increased, and the number of students who had misconceptions and did not understand the idea decreased. In the HOLS aspect, the most significant number of student answers were at the FSL level in terms of explaining the types of chemical bonds and depicting Lewis structures and in the explanation related to the possibility of compounds formed and the formation process of certain elements, the most significant number of student answers were at the NSL level. In the aspect of attitude, the learning outcomes show that most students’ answers are at the NSL level. In this study, it can be seen that students' chemical literacy skills with problem-based learning have not been able to provide significant changes. Therefore, further steps are needed to improve the learning process that can support students’ chemical literacy skills.